Urban environments’ impacts on aging in post-industrial cities: reviewing the pathways to healthy aging - Zhao, Hongsheng; Spada, Marco; Bortone, Ilaria (Frontiers in Medicine, 2025)
Post-industrial cities are characterized by an aging population, deteriorating urban infrastructure, and a range of socio-environmental challenges, including pollution, economic decline, and out-migration. These conditions, alongside the legacies of industrial decline, make aging in such environments considered particularly challenging when studied through the lens of conventional analytical frameworks such as active aging and age-friendly cities and communities (AFCC). By examining the literatures critically and analyzing unique spatial and social features of the environment of post-industrial cities, the paper expands the discussion regarding the impacts of environments on the healthy aging process within a post-industrial context. Based on 42 selected articles as evidences in exploring association of healthy aging and post-industrial built environment, this review implies that despite the negative perceptions, post-industrial city and community’s strong social networks within their long-established communities identities hold untapped potential to play positive roles in the pathways to healthy aging. This fresh perspective challenge prevailing assumptions on aging in post-industrial cities, offering a more nuanced understanding of the strengths and opportunities inherent in post-industrial contexts for supporting the healthy aging of elderly residents.